2011
DOI: 10.1002/ceat.201000421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microchannel Geometry on High‐Pressure Dispersion and Emulsification

Abstract: Experimental investigations of the effect of microchannel geometry on high-pressure dispersion and emulsification were carried out. Customized microchannels of varying geometric principles were fabricated in silicon and steel. In order to characterize the process efficiency of microchannel geometries, the effects of the process parameters (mean velocity, Reynolds number, and local pressure drop) were examined and correlated to the dispersion and emulsification results. It is demonstrated that high pressure los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…17,23 Further, there are also experimental studies on nanoemulsion which do not use any theoretical prediction and fit their droplet size data using empirical power law correlations. 19,[37][38][39][40] For instance, experimental studies have shown that nanoemulsion size increases with increase in droplet viscosity (m d ) and decreases with increase in continuous phase viscosity (m c ). 29,37,40 Hence, this article focuses on bridging the gap between experimental observations and theoretical predictions for nanoemulsion droplet size.…”
Section: Introductionmentioning
confidence: 99%
“…17,23 Further, there are also experimental studies on nanoemulsion which do not use any theoretical prediction and fit their droplet size data using empirical power law correlations. 19,[37][38][39][40] For instance, experimental studies have shown that nanoemulsion size increases with increase in droplet viscosity (m d ) and decreases with increase in continuous phase viscosity (m c ). 29,37,40 Hence, this article focuses on bridging the gap between experimental observations and theoretical predictions for nanoemulsion droplet size.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its hardness, stainless steel offers a good biocompatibility for pharmaceutical applications. More details concerning the developed designs and the investigations on the dispersion effect are reported by Gothsch et al (2011).…”
Section: Dispersion Micromodulementioning
confidence: 99%
“…Several works [8][9][10][11] were performed to estimate the flow uniformity in a single microchannel plate based on mathematical models or numerical simulation. With respect to mathematical models, Commenge et al [10] investigated the features of fluid flow through microchannel reactors by an approximate pressure drop model.…”
Section: Introductionmentioning
confidence: 99%